Liver abscess as a rare complication of Crohn's disease: A case report - Çetin KARACA; Binnur PINARBAŞI; Ahmet DANALIOĞLU; Filiz AKYÜZ; Sebahattin KAYMAKOĞLU; Sadakat ÖZDİL; Güngör BOZTAŞ; Zeynel MUNGAN (Turkish Journal of Gastroenterology, 2019)
-